Clinical Significance of Ventricular Tachyarrhythmias in Patients Undergoing Valve Replacement: A Nationwide Population-Based Study - Li, Guan-Yi; Chen, Yun-Yu; Chien, Kuo-Liong; Lin, Yenn-Jiang; Kuo, Tzu-Ting; Chung, Fa-Po (Frontiers in Cardiovascular Medicine, 2021)
Background: The clinical significance and outcomes of ventricular tachyarrhythmias (VTa) in patients undergoing valve replacement have rarely been reported. Objective: This study aimed to investigate the incidence and outcome of VTa after surgical valve replacement. Methods: We conducted a population-based retrospective cohort study using data obtained from the Taiwan National Health Insurance Research Database. In total, 10,212 patients were selected after 1:1 propensity-score matching based on the type of prosthetic valve used (mechanical versus bioprosthetic). Various outcomes during long-term follow-up were analyzed. Results: After a median follow-up period of 59.6 months, the crude incidence rate of VTa after surgical valve replacement was 4.8/1,000 person-years, and the cumulative incidence of VTa persistently increased after surgery. Furthermore, the occurrences of VTa after valve replacement significantly increased the risk of cardiovascular (CV) death (P<0.001, HR 1.67, 95% CI 1.41-1.96), stroke- (P<0.001, HR 1.66, 95% CI 1.37-2.01), atrial fibrillation- (P<0.001, HR 2.80, 95% CI 2.42-3.24), and congestive heart failure-related hospitalization (P<0.001, HR 2.61, 95% CI 2.30-2.95). Among patients with VTa, all-cause mortality (P=0.001, HR 0.49, 95% CI 0.32-0.75) and CV death (P=0.047, HR 0.58, 95% CI 0.34-0.99) in those with implantable cardioverter-defibrillator (ICD) implantation were lower than those without. Conclusion: The crude incidence rate of VTa after surgical valve replacement was 4.8/1,000 person-years, and the cumulative incidence of VTa persistently increased during follow-up. The presence of VTa after surgical valve replacement increases hospitalization and CV death, while ICD implantation reduced the mortality rate in these patients.